HIV persists in CCR6+CD4+ T cells from colon and blood during antiretroviral therapy. (2nd January 2017) - Gosselin, Annie; Wiche Salinas, Tomas Raul; Planas, Delphine; Wacleche, Vanessa S.; Zhang, Yuwei; Fromentin, Rémi; Chomont, Nicolas; Cohen, Éric A.; Shacklett, Barbara; Mehraj, Vikram; Ghali, Maged P.; Routy, Jean-Pierre; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: The objective of this article is to investigate the contribution of colon and blood CD4 + T-cell subsets expressing the chemokine receptor CCR6 to HIV persistence during antiretroviral therapy. Design: Matched sigmoid biopsies and blood samples ( n = 13) as well as leukapheresis ( n = 20) were collected from chronically HIV-infected individuals receiving antiretroviral therapy. Subsets of CD4 + T cells with distinct differentiation/polarization profiles were identified using surface markers as follows: memory (TM, CD45RA − ), central memory (TCM ; CD45RA − CCR7 + ), effector (TEM/TM ; CD45RA − CCR7 − ), Th17 (CCR6 + CCR4 + ), Th1Th17 (CCR6 + CXCR3 + ), Th1 (CCR6 − CXCR3 + ), and Th2 (CCR6 − CCR4 + ). Methods: We used polychromatic flow cytometry for cell sorting, nested real-time PCR for HIV DNA quantification, ELISA and flow cytometry for HIV p24 quantification. HIV reactivation was induced by TCR triggering in the presence/absence of all-trans retinoic acid. Results: Compared with blood, the frequency of CCR6 + TM was higher in the colon. In both colon and blood compartments, CCR6 + TM were significantly enriched in HIV DNA when compared with their CCR6 − counterparts ( n = 13). In blood, integrated HIV DNA levels were significantly enriched in CCR6 + versus CCR6 − TCM of four of five individuals and CCR6 + versus CCR6 − TEM of three of five individuals. Among blood TCM, Th17 and Th1Th17 contributed the most to the pool of cells harboring integrated HIV DNA despite their reduced frequency compared with Th2, which were infected the least. HIV reactivation was induced by TCR triggering and/or retinoic acid exposure at higher levels in CCR6 + versus CCR6 − TM, TCM, and TEM . Conclusion: CCR6 is a marker for colon and blood CD4 + T cells enriched for replication-competent HIV DNA. Novel eradication strategies should target HIV persistence in CCR6 + CD4 + T cells from various anatomic sites.